Old Russian spiritual and moral values in N.M. Karamzin's short story 'Poor Liza' - N.G. Komar (Ученые записки Казанского университета: Серия Гуманитарные науки)
The present paper aims to analyze the poetics of N.M. Karamzin's short story “Poor Liza”. It addresses the problem of coexistence of Old Russian and West European literary traditions while depicting relationships, representing family and family values. The study has revealed the connection between artistic elements of the short story, such as artistic detail, artistic discourse, and the traditions of Old Russian literature and West European literature. The following methods have been used in order to achieve the aim: comparative-historical, biographical, and evolutional. Along with N.M. Karamzin's “Poor Liza” and “The Knight of Contemporary World”, the sources include “The Tale of Peter and Fevronia of Murom” by Hermolaus-Erasmus, “Station Master” by A.S. Pushkin, “The Old World Landowners” by N.V. Gogol, and “The Storm” by A.N. Ostrovsky. The paper provides a number of examples which demonstrate the presence of West European traditions in the short story “Poor Liza”, especially when depicting love troubles and love relationships. These traditions clash with the Old Russian literary tradition based on the Gospel idea of love. Nevertheless, there are examples which testify to the evident presence of Old Russian literary traditions in the story. The analysis of some artistic elements in the short story “Poor Liza” has made it possible to conclude that it combines two literary traditions. In certain points, the form of perception and representation of love sentiments and love relationships, family and family values are absolutely opposite. However, N.M. Karamzin's artistic mentality is characterized as the one where these opposing spiritual and moral sets of norms typical of two different literary traditions coexist and do not openly confront each other. The conclusion presents the evolution of N.M. Karamzin's artistic worldview. His creation becomes increasingly devoted to the history and culture of Old Russia. The results obtained can be helpful in further research on N.M. Karamzin's poetology.